Consumer’s perception toward islamic home financing case study at: Ibu Pejabat Polis Kontinjen Kelantan / Nur Asyikin Mohamad - Mohamad, Nur Asyikin (2016)
There are some issue regarding Bay Bithaman Ajil (BBA) which is there are some consumers unsatisfied with the prevailing mode of BBA financing because the bank’s profit resulting to high price. Main focused of this research is to study about consumer’ perception toward Islamic home financing. The objective of this research is to study about the significant relationship between shariah compliant, computation and pricing, justice and equity and societal well-being. The study is used primary data by questionnaires and the sample consisted of 217 respondents and target population at Ibu Pejabat Polis Kontinjen Kelantan. The results revealed that shariah compliant and computation and pricing have a significant relationship between consumer’s perceptions. Meanwhile, the justice and equity and societal well-being have no significant relationship between consumer’s perceptions. Finally, the recommendation for Islamic banks they need to give more awareness to their customers regarding products that have an Arabic term it is because not all customers know about the features